Diversity of Mycobacterium tuberculosis Isolates from New Pulmonary Tuberculosis Cases in Addis Ababa, Ethiopia. (22nd November 2012) - Mihret, Adane; Bekele, Yonas; Loxton, Andre G.; Jordan, Annemie M.; Yamuah, Lawrence; Aseffa, Abraham; Howe, Rawleigh; Walzl, Gerhard
Abstract : Understanding the genetic diversity of Mycobacterium tuberculosis is needed for a better understanding of the epidemiology of TB and could have implications for the development of new diagnostics, drugs, and vaccines. M. tuberculosis isolates were characterized using spoligotyping and were compared with the SpoIDB4 database of the Pasteur Institute of Guadeloupe. A total of 53 different patterns were identified among 192 isolates examined. 169 of the isolates were classified into one of the 33 shared SITs, whereas the remaining 23 corresponded to 20 orphan patterns. 54% of the isolates were ascribed to the T family, a family which has not been well defined to date. Other prominent families were CAS, Haarlem, LAM, Beijing, and Unknown comprising 26%, 13%, 2.6%, 0.5%, and 2.1%, respectively. Among HIV-positive patients, 10 patterns were observed among 25 isolates. The T (38.5%), H (26.9%), and CAS (23.1%) families were the most common among HIV-positive individuals. The diversity of the M. tuberculosis strains found in this study is very high, and there was no difference in the distribution of families in HIV-positive and HIV-negative TB patients except the H family. Tuberculosis transmission in Addis Ababa is due to only the modern M. tuberculosis families (CAS, LAM, T, Beijing, Haarlem, and U).